Heat transfer and stress evolution behaviours of an aluminium alloy low pressure shell casting. Issue 1 (May 2015) - Zhang, D Q; Zhou, J X; Chen, T
Abstract: Considering the solidification, demoulding and heat treatment processes in low pressure casting, relatively complete processes of an aluminium alloy shell casting are simulated to investigate the heat transfer feature and stress behaviours variation of casting in each multi-processes stage. FDM is used to discrete thermal conduction model when studying the heat transfer process, while FEM is adopted to solve the elastic-plastic model when studying the stress behaviour variation. When matching the two models, we map the finite difference mesh to finite element mesh. Three different temperature conditions, namely 300 °C, 400 °C and 500 °C, are simulated when we research the influence of demoulding temperature on stress behaviour. The simulation results demonstrate that the higher demoulding temperature is, the greater casting deformation and the smaller stress value are. The final casting stress status and the initial heat treatment temperature have a different relationship as for different parts of casting.